Brexit and Article 50 of the Treaty of the European Union: Implications for UK Energy Policy and Security - Augustine O. Ifelebuegu; Kenneth E. Aidelojie; Elijah Acquah-Andoh (Energies, 2017)
This paper articulates the potential implications of Brexit on energy policy and security in the United Kingdom (UK). Given the uncertainties associated with the decision to leave the European Union (EU), the need to consider its potential effects on the UK’s energy sector becomes even more pertinent. Through the lens of a few widely reviewed trade regimes in the light of Brexit, it can be observed that while UK energy policies are unlikely to change drastically, Brexit nevertheless threatens the UK’s capacity to safeguard its energy supply. The uncertainties following Brexit could arguably starve the UK’s upstream petroleum, electricity, and renewable energy sectors of their required investments. Both short and long-term impacts could result in UK residents paying more per unit of energy consumed in a “hard Brexit” scenario, where the UK exits the Internal Energy Market (IEM) and must trade with the EU under World Trade Organisation rules. While a hard Brexit could aid the growth of the nascent shale gas industry, a negotiated withdrawal that includes some form of access to the IEM (a “soft Brexit”) would be more beneficial for the future of energy security in the UK.